Species-specific mechanisms of benthic foraminifera in response to shell dissolution - Daviray, Maxime; Lesut, Milla; Geslin, Emmanuelle; Metzger, Edouard; van Dijk, Inge; Courtial, Julia (Marine micropaleontology, 2025)
Ammonia confertitesta and Haynesina germanica are two common estuarine benthic foraminifera subject to sediment acidification. Nevertheless, mechanisms involved in their response to acidification are still poorly understood. Since H. germanica is kleptoplastic and photosynthetically active, unlike A. confertitesta, these species were cultured in controlled experiments to determine whether these mechanisms could mitigate acidification-induced shell dissolution. Both living and dead specimens were incubated at two pH (8.0 and 6.8) and two light conditions (0 and 24 μmol photon m-2.s-1) for 18 days. For each species, respiration and photosynthesis rates were calculated based on oxygen measurements. At the end of incubation, foraminiferal viability was assessed with CellTracker Green™ biomarker, and each test was categorised according to a dissolution scale (DS) using SEM. For both species, in acidic conditions, the tests of dead specimens were significantly more dissolved than the tests of living specimens, suggesting active mechanisms providing tolerance to acidification. For the living specimens, no significant difference in the DS distribution was observed between the two species at both conditions, suggesting that kleptoplast photosynthetic activity in H. germanica does not provide additional resistance to acidification. Until at least day 12, respiration data revealed a different biological activity for the two species, and we observed distinct behaviours (e.g., encystment and pseudopod emission). These suggest each species exhibits species-specific responses to cope with acidification. On day 18, respiration rates and binocular observations showed low biological activity, suggesting dormancy or death. Further investigation is required to identify the cellular mechanisms involved to counter acidification stress. •Living specimens and empty tests of two benthic foraminifera species were cultured in different pH and light conditions.•In acidic conditions, greater dissolution of empty tests compared to living specimens was observed.•No differences in the degrees of dissolution between the two species were observed.•Living foraminifera have active mechanism(s) to tolerate acidification.